Regulation of osteoclastogenesis by mast cell in rheumatoid arthritis - Kim, Kyoung-Woon (Arthritis Res Ther, 2021)
BACKGROUND: In the pathogenesis of rheumatoid arthritis (RA), the role of mast cells has not been revealed clearly. We aimed to define the inflammatory and tissue-destructive roles of mast cells in rheumatoid arthritis (RA). METHODS: Serum and synovial fluid (SF) concentration levels of tryptase, chymase, and histamine were quantified using ELISA. After activating mast cells using IL-33, the production of TNF-α, IL-1β, IL-6, IL-17, RANKL, and MMPs was determined using real-time PCR and ELISA. Osteoclastogenesis was assessed in CD14+ monocytes from peripheral blood and SF, which were cultured with IL-33-activated mast cells, by counting TRAP-positive multinucleated cells. RESULTS: The concentration levels of serum tryptase, chymase, and histamine and SF histamine were higher in patients with RA than in controls. FcεR1 and c-kit-positive mast cells were higher in RA synovium than in osteoarthritic (OA) synovium. Stimulation of mast cells by IL-33 increased the number of trypatse+chymase− and tryptase+chymase+ mast cells. IL-33 stimulation also increased the gene expression levels of TNF-α, IL-1β, IL-6, IL-17, RANKL, and MMP-9 in mast cells. Furthermore, IL-33 stimulated human CD14+ monocytes to differentiate into TRAP+ multinucleated osteoclasts. When CD14+ monocytes were co-cultured with mast cells, osteoclast differentiation was increased. Additionally, IL-33-activated mast cells stimulated osteoclast differentiation. The inhibition of intercellular contact between mast cells and monocytes using inserts reduced osteoclast differentiation. CONCLUSIONS: IL-33 increased inflammatory and tissue-destructive cytokines by activation of mast cells. Mast cells stimulated osteoclast differentiation in monocytes. Mast cells could stimulate osteoclastogenesis indirectly through production of tissue-destructive cytokines and directly through stimulation of osteoclast precursors.